2020
DOI: 10.3390/su12051850
|View full text |Cite
|
Sign up to set email alerts
|

Business Strategy, State-Owned Equity and Cost Stickiness: Evidence from Chinese Firms

Abstract: This paper investigates the relationship between business strategy and cost stickiness under different ownership. Using the data from listed firms in China from 2002 to 2015, we find that first, firms with different strategies exhibit different cost behavior. The cost stickiness of choosing a differentiation strategy is higher than that of choosing a low-cost strategy. Second, management expectations will affect cost stickiness. Optimistic expectations will increase cost stickiness, while pessimistic expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…In the face of the increase of product market competition, the management does not actively reduce the redundant cost, and there is the problem of soft budget constraint (Lin & Li, 2008, Lin & Tan, 1999 (Naughton, 2017;Zheng et al, 1998). In model 2, the coefficient of cost stickiness of differentiated strategic enterprises is 0.063% and 0.070% higher than that of cost-leading strategic enterprises respectively, which shows that in the Chinese cost-oriented industrial environment, the cost stickiness of enterprises implementing differentiated strategy is higher than that of enterprises implementing cost-leading strategy (Zhong et al, 2020). The coefficient of…”
Section: Regression Testmentioning
confidence: 94%
See 4 more Smart Citations
“…In the face of the increase of product market competition, the management does not actively reduce the redundant cost, and there is the problem of soft budget constraint (Lin & Li, 2008, Lin & Tan, 1999 (Naughton, 2017;Zheng et al, 1998). In model 2, the coefficient of cost stickiness of differentiated strategic enterprises is 0.063% and 0.070% higher than that of cost-leading strategic enterprises respectively, which shows that in the Chinese cost-oriented industrial environment, the cost stickiness of enterprises implementing differentiated strategy is higher than that of enterprises implementing cost-leading strategy (Zhong et al, 2020). The coefficient of…”
Section: Regression Testmentioning
confidence: 94%
“…Anderson et al (2003) first put forward the concept of cost stickiness, and confirmed the existence of cost stickiness in American listed companies based on the empirical research. Cost stickiness is also a pervasive phenomenon in China (Xu & Sim, 2017; Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations